″Model of formation of readiness of the head of a vocational educational institution for work in a competitive management team″. - Shalimova, I. (Problems of Engineer-Pedagogical Education, 2018)
The article deals with the problem of the formation of readiness of heads of vocational and technical educational institutions for work in a competitive management team. The article reveals and substantiates the conditions necessary for the development of readiness of the head of a vocational and technical educational institutions for work in the management team, provides descriptions of personality characteristics indispensable for developing structural components of readiness for the professional activity (procedural-content and social motivation for management, professional competences, reflection of educational and professional achievements, social and work-related communication skills, sense of self-esteem, etc.); the model and program of formation of psychological readiness of the head of a vocational institution for work in a competitive management team was developed and experimentally tested. The essence of the concept of "psychological readiness to work in a competitive management team" is expanded and supplemented together with the content-semantic contents of the component structure of the phenomenon under study. The article states that the developed program of forming the readiness of the head of a vocational educational institution for work in a competitive management team can be used by practical psychologists, heads of educational institutions of different types and forms of ownership.